The Symbolism of the Caravaca Cross in the Work “Crux Christi Salva Nos” by Szymon Godziemba-Trytek - Godziemba-Trytek, Szymon (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. The author’s commentary of Szymon Godziemba-Trytek concerns the role of sacred symbol in his work “Crux Christi Salva Nos” for mixed choir, soloists, horns, double basses and percussion (2017). This study for the first time acquaints the Ukrainian audience with the creativity of a modern Polish composer, who fruitfully works in the field of symphonic, chamber, and especially vocal and choral music. Main Objective of the article is to show the author’s way of interpreting sacred symbols in the composition and drama of his work; to reveal the role of a symbol as a tool for integrating a composition into an intercultural context that arises on the basis of musical and extra-musical listening experience. Methodology/How the study was done. The empirical and analytical methods used in the research reflect the two sides of the author’s activity — he is a composer and a scientist. From the Christian symbol of Caravaca Cross that inspired him — to the compositional idea and its implementation in sounds: these are the stages of the creative process described in the article. Results/Findings and Conclusions. The composition of the work «Crux Christi Salva Nos» was determined by two aspects of the European Christian symbol Caravaca Cross — its graphics and the history of its existence in culture. The external feature of the Caravaca Cross is the mnemonic signs applied to its surface, they fix the sequence of prayer lines. The sequence of the placement of these signs forms the architectonics of Godziemba-Trytek’s musical work. The symmetry in the arrangement of the signs corresponds to the symmetry of the music composition. In the history of the existence of Caravaca Cross in European culture, the composer is most attracted by the emergence of various religious cults associated with it. They origins often are in folklore. Reflections on the process of acceptance of theological ideas among the people led the composer to some decisions in the field of drama, performing resources, stylistics. Specially, composer use the text of the Polish traditional Lent Song as the epilogue of his work. This epilogue becomes the quiet climax of the composition. The choir’s location and the way haw it is used in the work are also symbolic: within each subsequent movement, the choir is situated closer to the listener. Stylistic means reflect the idea of giving the dogmas of faith a human dimension.